Implementation of Kitab Kuning Curriculum Management in Improving Student Quality at Hidayatul Al Mustafid Islamic Boarding School - Mustafit, Hidayatul (Wasatha: Jurnal Studi Islam dan Humaniora, 2026)
This research explores the implementation and impact of the Kitab Kuning curriculum at Pondok Pesantren Hidayatul Al Mustafid, focusing on its effectiveness in enhancing educational quality and student development. The study employs a qualitative, descriptive approach to evaluate the implementation and its effects on student quality. Data were collected through observations, interviews with administrators, teachers, and students, as well as document analysis. The findings indicate that the implementation of this curriculum positively impacts students’ understanding of religious teachings, critical thinking skills, and character formation. Challenges such as aligning with modern educational needs were identified. This research highlights the importance of balancing traditional values with contemporary educational needs to enhance the relevance of the Kitab Kuning curriculum.